Forecast of oil and gas reservoirs of the Sea of Okhotsk based on interpretation processing of seismic material - А. К. Shatyrov (Известия высших учебных заведений: Геология и разведка, 2023)
Background. This article analyses the results of geological and geophysical studies conducted in the Okhotsk Sea area with the purpose of developing methods for processing seismic information in combination with other data to solve the problems of forecasting hydrocarbon deposits.Aim. Solving problems of forecasting hydrocarbon deposits through the development of a structural and technological scheme for prospecting and evaluation of a geological and geophysical model to identify images of oil and gas deposits.Materials and methods. The research methodology included selection of the location of points for simulating “vertical wells” in order to analyze the geodynamics of the medium; multiplex parametric transformations of wave fields taking into account diagnostic significant attributes and building a multiparametric cluster; selection of oil and gas deposits; formation of images of oil and gas deposits; local forecast of improved reservoir properties and saturation; refinement of the geometry of target surfaces with forecast data in actual points (vertical wells); forecast of the area of target surfaces; spatial mapping of the largest hydrocarbon deposits.Results. Forecasting of oil and gas prospects in the Okhotsk Sea in areas where there is no deep drilling can be carried out using the following technologies: detailing the structural and tectonic structure of hydrocarbon traps; multi-feature prediction of hydrocarbon deposits; decomposition of the dispersion of the wave field; low-frequency resonance of seismic emission geodynamic noise; selection of oil and gas-containing objects.